2023
DOI: 10.3390/ijms24076512
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Wetting and Permeation Properties of Bio-Oil as Bitumen Rejuvenator

Abstract: In order to explore the diffusion and regeneration of bio-oil in aged bitumen, waste cooking oil (WCO), waste wood oil (WWO) and straw liquefied residue oil (SLRO) were selected in this paper. According to the surface wetting theory, the contact angle is obtained by combining laboratory experiments with molecular dynamics (MD) simulation, and the wetting parameters are calculated to evaluate the wetting behavior of bio-oil. The experimental phenomena of the wetting process and the main factors driving wetting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(71 reference statements)
0
0
0
Order By: Relevance
“…Zheng et al studied the regeneration effect of vegetable oil from the aspects of permeability and molecular level. They found that vegetable oil shows better compatibility with the aged asphalt binder, owing to its greater permeability and stronger molecular activity [22]. For the same aged asphalt binder, the amount of vegetable oil was only one-third that of the mineral oil-based regeneration agent to obtain the same regeneration effect [23].…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al studied the regeneration effect of vegetable oil from the aspects of permeability and molecular level. They found that vegetable oil shows better compatibility with the aged asphalt binder, owing to its greater permeability and stronger molecular activity [22]. For the same aged asphalt binder, the amount of vegetable oil was only one-third that of the mineral oil-based regeneration agent to obtain the same regeneration effect [23].…”
Section: Introductionmentioning
confidence: 99%